Inter-Skeleton Conductive Routes Tuning Multifunctional Conductive Foam for Electromagnetic Interference Shielding, Sensing and Thermal Management - Li, Xufeng; Chen, Chunyan; Li, Zhenyang; Yi, Peng; Zou, Haihan; Deng, Gao; Fang, Ming; He, Junzhe; Sun, Xin; Yu, Ronghai; Shui, Jianglan; Pan, Caofeng; et al. (Nano-Micro Letters, 2024)
Conductive polymer foam (CPF) with excellent compressibility and variable resistance has promising applications in electromagnetic interference (EMI) shielding and other integrated functions for wearable electronics. However, its insufficient change amplitude of resistance with compressive strain generally leads to a degradation of shielding performance during deformation. Here, an innovative loading strategy of conductive materials on polymer foam is proposed to significantly increase the contact probability and contact area of conductive components under compression. Unique inter-skeleton conductive films are constructed by loading alginate-decorated magnetic liquid metal on the polymethacrylate films hanged between the foam skeleton (denoted as AMLM-PM foam). Traditional point contact between conductive skeletons under compression is upgraded to planar contact between conductive films. Therefore, the resistance change of AMLM-PM reaches four orders of magnitude under compression. Moreover, the inter-skeleton conductive films can improve the mechanical strength of foam, prevent the leakage of liquid metal and increase the scattering area of EM wave. AMLM-PM foam has strain-adaptive EMI shielding performance and shows compression-enhanced shielding effectiveness, solving the problem of traditional CPFs upon compression. The upgrade of resistance response also enables foam to achieve sensitive pressure sensing over a wide pressure range and compression-regulated Joule heating function. Highlights: 1 Unique inter-skeleton conductive films are constructed in polymer foam. 2 The resistance change of the foam can reach four orders of magnitude under compression. 3 This foam exhibits strain-adaptive electromagnetic interference shielding performance, anti-interference pressure sensor with high sensitivity over a wide pressure range and compression-regulated Joule heating function.